Update on the epidemiology of carbapenemases in Latin America and the Caribbean (2020)
Introduction: Carbapenemases are β-lactamases able to hydrolyze a wide range of β-lactam antibiotics, including carbapenems. Carbapenemase production in Enterobacterales, Pseudomonas aeruginosa, and Acinetobacter spp., with and without the co-expression of other β-lactamases is a serious public health threat. Carbapenemases belong to three main classes according to the Ambler classification: class A, class B, and class D. Areas covered: Carbapenemase-bearing pathogens are endemic in Latin America. In this review, we update the status of carbapenemases in Latin America and the Caribbean. Expert opinion: Understanding the current epidemiology of carbapenemases in Latin America and the Caribbean is of critical importance to improve infection control policies limiting the dissemination of multi-drug-resistant pathogens and in implementing appropriate antimicrobial therapy.